Modulated Ionomer Distribution in the Catalyst Layer of Polymer Electrolyte Membrane Fuel Cells for High Temperature Operation. Issue 8 (28th April 2014) - Choo, Min‐Ju; Oh, Keun‐Hwan; Kim, Hee‐Tak; Park, Jung‐Ki
Abstract Ionomer distribution is an important design parameter for high performance polymer electrolyte membrane fuel cells (PEMFCs); however, the nano‐scale modulation of the ionomer morphology has not been intensively explored. Here, we propose a new route to modulate the ionomer distribution that features the introduction of poly(ethylene glycol) (PEG) to the cathode catalyst layer and the leaching the PEG phase from the catalyst layer using a water effluent during operation. The key concept in the approach is the expansion of the ionomer thin film through the PEG addition. We demonstrate that the modulated ionomer distribution increases the electrochemical active area and proton transport property, without loss in oxygen transport, at a fixed ionomer content. At a high temperature of 120 °C, the power performance at 0.6 V is increased by 1.73‐fold with the modulated ionomer distribution as a result of 1.25‐fold increase in the electrochemical active area and two‐fold increase in the proton transport rate in the catalyst layer.